Disiplin Kerja, Budaya Organisasi, dan Kinerja Pegawai Pada Fakultas Ilmu Komputer Universitas Sriwijaya - Fenni Selvania; Martini Martini; Haikal Haikal (Politeknik Negeri Sriwijaya, 2021)
This study aims to analyze the effect of work discipline and organizational culture on employee performance. This research was conducted on 52 employees at the Faculty of Computer Science, Sriwijaya University. The results showed that the variables of work discipline and organizational culture had a positive and significant effect on employee performance both simultaneously and partially. Work discipline variables have a positive and significant effect on employee performance. The application of employee work discipline is very helpful for the company in achieving organizational goals. Organizational culture variables have a positive and significant effect on employee performance. Organizational culture can influence employee work behavior so that it can affect employee performance.Â